Artifacts IN Computed Radiography-A Review Article (Journal of Pharmaceutical Negative Results, 2022)
Background: Artifacts in radiography images are distracting and may sometimes influence interpretation. In appearance and cause, computed radiography (CR) systems can produce artifacts that differ from those observed in conventional film radiography. Various components utilized in digital photography have been associated with these artifacts. Computed radiography offers numerous advantages over conventional radiography. In recent years, its use has expanded due to new technologies and the development of other time-saving alternatives. However, like with any imaging technique, it is essential to be aware of the numerous artifacts that might lead to misdiagnosis. It appears hardware and software artifacts are comparable in their application to this topic. Radiographic artifacts are distracting and may precise diagnosis. Although most conventional radiography artifacts are well-known, computed radiography (CR) systems generate unique anomalies from those observed in traditional radiography. We have seen several artifacts in C.R. photographs taken by four specific plate readers. These distortions and operator errors have been associated with the imaging plate, plate reader, image processing software, or laser printer. In this article, many computed radiography artifacts are shown, some of which can be used to mimic pathologic injuries. Their root causes and potential remedies are briefly covered. Over the past five years, there has been an increase in the number of computed radiography systems with photostimulable storage phosphors installed in radiology departments across the globe. The image quality and dependability of the equipment have both been outstanding. However, there have been various perplexing artifacts, some of which mimic actual illness. Computed radiographic systems can modify the severity or appearance of non-computed radiographic artifacts (fogging, double exposure, foreign substances, etc.)